2000
DOI: 10.1034/j.1600-0749.2000.130105.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis

Abstract: The response of cells to extracellular signals usually requires altered expression of many genes, possibly including several distinct metabolic pathways. In some cases, only a subset of genes involved in such responses are known, which requires techniques to analyze changes in the expression of multiple genes, both known and unknown. Three techniques, two‐dimensional gel electrophoresis, differential display, and gene discovery arrays, provide opportunities for measuring changes in gene expression levels, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Martin and collaborators (Martin et al, 2001) found that less than 10% (12/170) of the DD-isolated sequences spotted on a membrane gave useful results upon further analysis of additional patient samples. Several studies using PCR-DD and mAs as complementary approaches detected few genes (0-10) by both approaches (Outinen et al, 1998;Wells, 1999;Cirelli and Tononi, 2000;Oetting, 2000;Heilig and Sommer, 2004;Pascal et al, 2005). Our large-scale study permits a more extensive comparison of PCR-DD and arrays, and shows that the correlation is good if certain reasonable selection criteria are used.…”
Section: Methods and Strategymentioning
confidence: 66%
“…Martin and collaborators (Martin et al, 2001) found that less than 10% (12/170) of the DD-isolated sequences spotted on a membrane gave useful results upon further analysis of additional patient samples. Several studies using PCR-DD and mAs as complementary approaches detected few genes (0-10) by both approaches (Outinen et al, 1998;Wells, 1999;Cirelli and Tononi, 2000;Oetting, 2000;Heilig and Sommer, 2004;Pascal et al, 2005). Our large-scale study permits a more extensive comparison of PCR-DD and arrays, and shows that the correlation is good if certain reasonable selection criteria are used.…”
Section: Methods and Strategymentioning
confidence: 66%
“…Mutations in TYRP1 result in the inability to convert the brownish 5,6-dihydroxyindol into the blackish eumelanin, which affects the shade of brown color of wool [24,28]. KIT [19], MLPH [24], and KIF5A [29] are commonly recognized as genes that mediate the formation and distribution of pigment granules in melanocytes which are associated with the translocation of melanosomes. In contrast, the PMEL [27] gene is involved in melanosome structure, and its variation can inhibit melanosome formation, resulting in melanin dilution [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…People whose tyrosinase gene is inherently deleted or less expressed develop albinism or vitiligo disease. 9,10 The tyrosinasemediated reaction is based on oxidation in the active site of the enzyme. Without any cofactor, tyrosinase oxidizes phenolic moieties using only oxygen molecules.…”
Section: Introductionmentioning
confidence: 99%